Analysis of Implementation of Self-Reliance Development Policy Work Guidance for Correctional Families - Deby Chintia Hestiriniah; Wahda Chairunnisa Meidiningsih (Jurnal Office, 2022)
An analysis of the implementation of the policy of fostering independence of work guidance that has been carried out by the Class IIA Palembang Women's Prison which aims to provide skills and knowledge when serving prison prisoners and preparing fostered residents for correctional activities to return to the community and improve the social functioning of fostered residents in correctional services. This study aims to identify and analyze the implementation of the policy of fostering self-directed work guidance that has been carried out by the Class IIA Palembang Women's Prison. This research is a descriptive research with an occlusive approach. o The data used o is based on the o type o is oqualitative data, while based on the source o is primary primary data and secondary o data. o The open data collection instruments used were documentation, interviews, and observations. Based on the research results, there are 3 dimensions that have not gone well, namely the standard dimensions and policy targets/measures and policy objectives, resources and attitudes of implementers. The dimensions that have been running well are the dimensions of the implementing organization's characteristics, communication between related organizations and the socio-economic and political environment. So it can be concluded that the implementation of the policy of fostering independence of work guidance has not been able to return convicts to the community by providing life provisions in the form of work skills, because in essence prisons aim to make convicts become better citizens than before by instilling good personality and character.